(untitled) (International Journal of Engineering and Computer Science, 2017)
Positioning based services really picked up pace in the early 90’s which came with the emergency response lines like 911, 100, etc. and which due public awareness regarding the location services being offered. These services also extend to the transport and logistics side an example of which would be that nowadays taxies have inbuilt location bases services to track the vehicles. There are multiple positioning based services available like GPS, GLONASS, Time of Arrival, Angle of Arrival, etc. with each having their own pros and cons. We shall cover some of these services and review them for their functioning and functionality